Benign melanocytic lesions with emphasis on melanocytic nevi – A histomorphological analysis (Journal of Pathology of Nepal, 2018)
Background: Melanocytic lesions are common and include both benign and malignant conditions. Benign melanocytic nevus may show varied microscopic features and should be differentiated from malignant lesions. In the present study, we analyse the histopathological pictures of different types of benign melanocytic nevi.Materials and methods: This study was a hospital based retrospective study and all the cases reported as melanocytic nevus in the period from Jan 2014 to June 2018 in the Department of Pathology, Manipal Teaching Hospital were retrieved and analysed in the study.Results: A total of 104 melanocytic lesions including 74 cases of benign melanocytic nevus were reported in the study period. Females were affected more with a female to male ratio of 1.8:1. The age range was 5 to 78 years with mean age of 28 years. Among the female patients, the commonest age group was 21-30 years while among the males; the most affected age group was 11-20. The commonest histopathological subtype was intradermal nevus comprising 73% cases followed by compound nevus.  On analysis of the different sites involved, face, head and neck were found to comprise 92% cases. Epidermal changes including hyperkeratosis, acanthosis were common in intradermal nevus. In most cases, tumor cells were arranged in nests. Melanin pigment was noted in majority of the cases. Secondary changes noted were chronic inflammation, fibrosis and multinucleated giant cells.Conclusion: Benign melanocytic nevus may present in varied age range and show wide spectrum of histological features. All pigmented lesions should be biopsied for its subtypes.